Pengaruh Lamanya Waktu Tunggu (Waiting Time) Kapal Terhadap Efisiensi Proses Kegiatan Discharge dan Loading Batu Bara pada PT Adhika Samudera Jaya - Ais Sanda Putra Trisna; Faris Nofandi; Vigih Hery Kristanto; Maulidiah Rahmawati (Journal Of Business, Finance, and Economics (JBFE), 2025)
To support the smooth operation of activities at the port and jetty, adequate facilities and operational systems are required. Long waiting times can reduce the efficiency of the loading and unloading process and hinder other operational processes. Delays can increase the operational cycle of ships, raise operational costs, and decrease port productivity. This study aims to examine the impact of ship waiting time on the efficiency of the coal discharge and loading process at PT. Adhika Samudera Jaya. Efficiency in the loading and unloading activities is crucial for increasing productivity and reducing operational costs. The research employs a quantitative method, with data collection through direct observation and documentation. The results indicate that the duration of ship waiting time significantly affects the efficiency of the discharge and loading process, where longer waiting times lead to longer loading and unloading durations. Key factors influencing waiting time include equipment readiness, weather conditions, shipping management, and cargo availability. By improving operational planning and speeding up facility readiness, the efficiency of the coal discharge and loading process can be optimized. This finding is expected to serve as a reference for companies and port authorities in improving the quality of coal loading and unloading services.